Genome access and other web-based IT solutions: Genetic counseling in the digital era - Cazzaniga, Alessia; Plebani, Marta; Crimi, Marco (Frontiers in Public Health, 2022)
Genetic counselors are healthcare professionals who are trained in both medical genetics and counseling to help guide individuals through what is known about genetic predispositions toward a variety of diseases, how they are inherited, and what impact this information can have on them and their partners and families. The range and scope of practice of GC has greatly expanded beyond where it started and now, it is employed in a variety of clinical and research settings. The traditional approach to GC involves meeting with a counselor in person. However, with the increasing availability of online resources, more people are seeking information about genetic disorders online. This shift has led to the development of online GC services. Indeed, genetic counselors are no strangers to improvements in terms of adopting digital solutions in their clinical routine, however, there are few studies assessing genetic counselors’ attitudes regarding existing digital tools. Genome Access® is a digital platform that improves patient knowledge in the field of genetic diseases and supports specialists throughout different stages of counseling. This study aims to present Genome Access and discuss the importance of adopting digital technologies designed specifically for GC and what tools these solutions should include.